Transparency in the existence, use, and output of a mental health data resource: a descriptive paper from the National Institute for Health and Care Research (NIHR) Maudsley Biomedical Research Centre (BRC) Clinical Record Interactive Search (CRIS) Platform - Amelia Jewell; Matthew Broadbent; Claire Delaney-Pope; Megan Pritchard; Hannah Woods; Robert Stewart (International Journal of Population Data Science)
Background Transparency in the use of routinely collected mental health data for research is essential in maintaining public support and trust, as well as for supporting the sharing of information and data resources amongst the academic community. The National Institute for Health and Care Research (NIHR) Maudsley Biomedical Research Centre (BRC) Clinical Records Interactive Search (CRIS) enables a case register of deidentified mental health records from the South London and Maudsley NHS Foundation Trust (SLaM). CRIS supports mental health research across the lifespan from children and adolescents to older adults.